2015
DOI: 10.1097/scs.0000000000002006
|View full text |Cite
|
Sign up to set email alerts
|

Cranioplasty of Hemispherical Defects Using High Impact Methylmethacrylic Plate

Abstract: High Impact Acrylic is an excellent restorative material for reconstructing large sized cranial defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…PMMA properties, such as inertness, low cost, rigidity, easy preparation, biocompatibility etc. , make PMMA-based bone cements suitable for use in different health-related situations, body areas and procedures, such as in cranioplasty, in which it has been used since the second world war [ [12] , [13] , [14] ]. PMMA has been the most widely used material for correction of bony defects of the skull and face, mainly for cosmetic reasons [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…PMMA properties, such as inertness, low cost, rigidity, easy preparation, biocompatibility etc. , make PMMA-based bone cements suitable for use in different health-related situations, body areas and procedures, such as in cranioplasty, in which it has been used since the second world war [ [12] , [13] , [14] ]. PMMA has been the most widely used material for correction of bony defects of the skull and face, mainly for cosmetic reasons [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the patients' and/or family members' reluctance about a second surgical procedure, we decided to use UK treatment. The mean epidural hematoma volume was 1). Almost all the patients (14 of 15) recovered without any additional complications and were discharged from the hospital, except for one patient who underwent ventriculoperitoneal shunt insertion and cranioplasty simultaneously.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies demonstrated that cranioplasty protects the brain and improves cosmesis. 1,2 However, cra-nioplasty is associated with several complications that affect up to 34% of patients including infections, hematoma formation, poor cosmesis, seizures, and cerebrospinal fluid (CSF) leakage. 2,3 Postoperative epidural hematomas often lead to further surgical interventions, intracerebral mass effect, death, 4,5 and poor wound healing that can be attributed to the prolonged interval of wound drainage.…”
Section: Introductionmentioning
confidence: 99%
“…36 Another factor that contributes to bone resorption is the method of bone storage because freeze-dried bone loses its vitality and undergoes unpredictable resorption. 37 Relevant information about bone grafts, which ideally would be included in this manuscript but was not provided by the authors, includes the area of the cranium that required rehabilitation, graft type, 7,11,24,25,26,28,30,31,32,33 and area from which the donor graft was obtained. 7,11,24,26,28,30,31,32,33 Alloplastic materials, such as PMMA, are considered good choice for patients who require secondary reconstruction with a custom-made CAD/ CAM device following a previous failed cranioplasty (contour deformity caused by significant bone graft resorption or implant/bone graft removal resulting from infection).…”
Section: Discussionmentioning
confidence: 99%